Impact of date powder, sacha inchi oil, and moringa powder in a novel cognitive-enhancing health bar: an evaluation of physicochemical properties and functional benefits - Mohd Noor, Nurul Auni; Hazahari, Noor Yuslida; Shahidan, Norshazila; Amid, Azura; Sofian Seng, Noor Soffalina (IIUM Press, 2024)
Recent trends show a growing preference for healthy snacks in diets, particularly among health-conscious consumers, with snack bars gaining popularity among youth. This study aimed to develop and analyse a nutritious health bar to enhance cognitive performance. The health bar's formulation was created using design expert software. Comprehensive testing included proximate analysis, fatty acid profiling, and vitamin, mineral, and antioxidant evaluations, complemented by texture and colour assessments. Findings reveal these bars to be nutritionally rich, featuring excellent physical characteristics. They are notably abundant in essential fats (omega-3 and omega-6), vitamins, and minerals. The bars' high essential fat content, varied vitamin and mineral composition, and strong antioxidant properties align with the Recommended Nutrient Intakes (RNI) for Malaysian children and adolescents. This composition suggests that these health bars could effectively boost cognitive performance in this group.